The anticancer multi-kinase inhibitor dovitinib also targets topoisomerase I and topoisomerase II - Hasinoff, Brian B. (2012)
Dovitinib (TKI258/CHIR258) is a multi-kinase inhibitor in phase III development for the treatment of several cancers. Dovitinib is a benzimidazole-quinolinone compound that structurally resembles the bisbenzimidazole minor groove binding dye Hoechst 33258. Dovitinib bound to DNA as shown by its ability to increase the DNA melting temperature and by increases in its fluorescence spectrum that occurred upon the addition of DNA. Molecular modeling studies of the docking of dovitinib into an X-ray structure of a Hoechst 33258-DNA complex showed that dovitinib could reasonably be accommodated in the DNA minor groove. Because DNA binders are often topoisomerase I (EC 5.99.1.2) and topoisomerase II (EC 5.99.1.3) inhibitors, the ability of dovitinib to inhibit these DNA processing enzymes was also investigated. Dovitinib inhibited the catalytic decatenation activity of topoisomerase IIα. It also inhibited the DNA-independent ATPase activity of yeast topoisomerase II which suggested that it interacted with the ATP binding site. Using isolated human topoisomerase IIα, dovitinib stabilized the enzyme-cleavage complex and acted as a topoisomerase IIα poison. Dovitinib was also found to be a cellular topoisomerase II poison in human leukemia K562 cells and induced double-strand DNA breaks in K562 cells as evidenced by increased phosphorylation of H2AX. Finally, dovitinib inhibited the topoisomerase I-catalyzed relaxation of plasmid DNA and acted as a cellular topoisomerase I poison. In conclusion, the cell growth inhibitory activity and the anticancer activity of dovitinib may result not only from its ability to inhibit multiple kinases, but also, in part, from its ability to target topoisomerase I and topoisomerase II.